Variable frequency drive trainer kits for electronic control system subjects in vocational secondary schools - Mustofa Abi Hamid; Putu Sudira; Mochamad Bruri Triyono; Muhamad Aqil Rizqillah; Irwanto Irwanto; Dedi Setiawan; Desmira Desmira; Martias Martias; Muhammad Hakiki; Tamil Selvan Subramaniam; Abdurrahman Abdurrahman (Institute of Advanced Engineering and Science, 2024)
The objective of this study is to create a variable frequency drive (VFD) trainer kit, assess the practicality of the developed VFD educational tool, and evaluate its impact on the academic performance of industrial electronic engineering students, particularly in the area of electronic control systems. The study utilizes the ADDIE model and customized to meet the requirements and consists of the following phases: analysis, design, development, implementation, and evaluation. There were 130 respondents consisting of 122 vocational students, 1 industry expert/practitioner in the field of VFD, 1 vocational training center instructor, 4 vocational teachers, and 2 lecturers. Data were collected using questionnaires with 4 Likert scales from strongly agree to strongly disagree, feasibility assessment sheets from media experts and material experts, interviews, and electronic control system learning outcomes tests. The learning media receives a “highly feasible” and the job sheet obtains 67 “highly feasible”. Moreover, the level of effectiveness of the learning media receives a score of 0.724, indicating high effectiveness. Therefore, they have proven to be effective in enhancing student learning outcomes and developing their proficiency in controlling the speed of electric motors. This will help bridge the gap between the industry's skill requirements and the skills taught in schools.